Dynamic Simulation Approach for Liquid Loading in Horizontal Gas Well X Field Indonesia - Hairuni Hapsari; Dwi Atty Mardiana; Shabrina Sri Riswati; Pri Agung Rakhmanto (Penerbitan Universitas Trisakti, 2022)
There has been intensive investigation on the understanding of the liquid loading phenomenon lately via experiment and transient approach. This is driven due to the limitation of the traditional approach using steady state Turner correlation to be used over a wide range of actual conditions (i.e such as under various tubing diameters, fluid condition (CGR/WGR), and horizontal or deviated trajectory of the well) which can lead to underpredict critical gas rate and mitigation action which directly impact the production and economics limit of the field. By nature, the liquid loading phenomena classified as transient or dynamic phenomena and hence couldn’t be able to be explained under the steady state approach. The application of dynamic well modeling itself has been applied worldwide recently. Therefore, utilizing this new approach for estimating the critical gas rate for horizontal well bring benefit by reducing the uncertainty of the outcome and providing more accurate prediction compare to the traditional approach. The selection of the de-liquification method which uses the bullheading for the horizontal gas well in X field provides the highest production optimization and the most economical approach to the field as there is no additional opex cost required.